Early life nutritional programming of health and disease in The Gambia. (27th October 2015) - Moore, S. E.
Abstract : Exposures during the early life (periconceptional, prenatal and early postnatal) period are increasingly recognized as playing an important role in the aetiology of chronic non-communicable diseases (NCD), including coronary heart disease, stroke, hypertension, Type 2 diabetes and osteoporosis. The 'Developmental Origins of Health and Disease' (DOHaD) hypothesis states that these disorders originate through unbalanced nutrition early in life and risk is highest when there is a 'mismatch' between the early- and later-life environments. Thus, the DOHaD hypothesis would predict highest risk in countries where an excess of infants are born with low birth weight and where there is a rapid transition to nutritional adequacy or excess in adulthood. Here, I will review data from work conducted in rural Gambia, West Africa. Using demographic data dating back to the 1940s, the follow-up of randomized controlled trials of nutritional supplementation in pregnancy and the 'experiment of nature' that seasonality in this region provides, we have investigated the DOHaD hypothesis in a population with high rates of maternal and infant under-nutrition, a high burden from infectious disease, and an emerging risk of NCDs.